ANALISIS FAKTOR-FAKTOR KEUANGAN YANG MEMPENGARUHI UNDERPRICING PADA PENAWARAN SAHAM PERDANA - Abdurrosyid, Muhammad (Jurnal Akuntansi AKUNESA, 2013)
Underpricing is conditions which show that open price at primary market was more lower than close price at secondary market. This phenomenon creates uncertainty for companies including investor to invest. This uncertainty can be minimized by analyzing financial factors, such as ROE, DER, SIZE. This research used multiple linear regression analysis. The research object is property and real estate sector companies that are doing IPO at Indonesia stock exchange in 2008-2012. The samples used in research as much as 9 property and real estate sector companies chosen by purposive sampling technique. The results of research showed financial factors above not having significant effect to underpricing. Keywords : underpricing, ROE, DER, SIZE